Late-Onset Microsporidial Keratitis in Femtosecond Astigmatic Keratotomy After Laser-Assisted Phacoemulsification. Issue 11 (November 2018) - Grillo, Lola M.; Epstein, Ilan J.; Donnenfeld, Eric D.; Perry, Henry D.
Abstract : Purpose: To present a case of microsporidial keratitis in a femtosecond laser–created astigmatic keratotomy (AK) incision. Methods: Case report. Results: A 65-year-old Middle Eastern man presented 2 months after uncomplicated femtosecond laser–assisted cataract surgery (FLACS) and AK with mildly decreased vision and corneal edema in the operative eye. Shortly after treatment with topical corticosteroids, a fulminant corneal infiltrate manifested along the temporal arcuate incision. Multiple corneal scrapings sent for laboratory analysis were inconclusive. Two weeks after the initial presentation, a deep tissue sample was obtained using a 27-gauge cannula passed within the arcuate incision. The gram stain was directly observed, revealing intracellular microsporidial spores. The patient was treated with oral albendazole 400 mg once daily over 2 weeks and topical voriconazole 1% and fumagillin 3 mg/mL eye drops over 10 weeks. During this course, visual function steadily recovered as the infiltrate coalesced and ocular inflammation subsided. Conclusions: This is the first reported case of microsporidial keratitis presenting as a late-onset infection after femtosecond laser–assisted AK.